Pathogenicity of Porphyromonas asaccharolytica in Adult Periodontitis of Malaysian Samples - Himratul-Aznita, W.H.; Mahmood, A.A. (Asian Network for Scientific Information, 2008)
Bacterial toxin of Porphyromonas asaccharolytica strains obtained from adult periodontitis were analysed using mouse model. Results from subcutaneous injection with whole bacterial cells of 108 and 1010 cells mL-1 failed to induce any infection. However when bacterial concentration of 1012 cells mL-1 was used, all P. asaccharolytica strains were able to induced the development of localized lesion on balb/c mice. In addition, infected mice appeared cachectic with ruffled hair. Thus, infection with the latter concentration was pathogenic and was dose dependent. The toxin was also found to be heat labile for all strains. Therefore, we conclude that the extracellularly toxin produced by P. asaccharolytica of our local isolates which were obtained from adult periodontitis, is virulent and heat labile.